Regional metabolic heterogeneity of the hippocampus is nonuniformly impacted by age and caloric restriction. Issue 1 (2nd November 2015) - Martin, Stephen A.; DeMuth, Tyler M.; Miller, Karl N.; Pugh, Thomas D.; Polewski, Michael A.; Colman, Ricki J.; Eliceiri, Kevin W.; Beasley, Timothy Mark; Johnson, Sterling C.; Anderson, Rozalyn M.
Summary: The hippocampus is critical for cognition and memory formation and is vulnerable to age‐related atrophy and loss of function. These phenotypes are attenuated by caloric restriction (CR), a dietary intervention that delays aging. Here, we show significant regional effects in hippocampal energy metabolism that are responsive to age and CR, implicating metabolic pathways in neuronal protection. In situ mitochondrial cytochrome c oxidase activity was region specific and lower in aged mice, and the impact of age was region specific. Multiphoton laser scanning microscopy revealed region‐ and age‐specific differences in nicotinamide adenine dinucleotide (NAD)‐derived metabolic cofactors. Age‐related changes in metabolic parameters were temporally separated, with early and late events in the metabolic response to age. There was a significant regional impact of age to lower levels of PGC‐1α, a master mitochondrial regulator. Rather than reversing the impact of age, CR induced a distinct metabolic state with decreased cytochrome c oxidase activity and increased levels of NAD(P)H. Levels of hippocampal PGC‐1α were lower with CR, as were levels of GSK3β, a key regulator of PGC‐1α turnover and activity. Regional distribution and colocalization of PGC‐1α and GSK3β in mouse hippocampus was similar in monkeys. Furthermore, the impact of CR to lower levels of both PGC‐1α and GSK3β was also conserved. The studies presented here establish the hippocampus as a highly varied metabolic environment, reveal cell‐type and regional specificity in the metabolic response to age and delayed aging by CR, and suggest that PGC‐1α and GSK3β play a role in implementing the neuroprotective program induced by CR.